2016
DOI: 10.1016/j.ijdevneu.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversities or high fat diet intake reduce cognitive function and alter BDNF signaling in adult rats: Interplay of these factors changes these effects

Abstract: Environmental factors, like early exposure to stressors or high caloric diets, can alter the early programming of central nervous system, leading to long-term effects on cognitive function, increased vulnerability to cognitive decline and development of psychopathologies later in life. The interaction between these factors and their combined effects on brain structure and function are still not completely understood. In this study, we evaluated long-term effects of social isolation in the prepubertal period, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 96 publications
0
22
2
2
Order By: Relevance
“…later in life. Pervious animal models by others have not recapitulated these human findings entirely (Tozuka et al, 2010; Zieba, Uddin, Youngson, Karl, & Morris, 2019) or found that the combination of two environmental insults rescued memory impairment (Arcego et al, 2016). Importantly, these other animal models employed different types and timing of environmental stressors on the offspring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…later in life. Pervious animal models by others have not recapitulated these human findings entirely (Tozuka et al, 2010; Zieba, Uddin, Youngson, Karl, & Morris, 2019) or found that the combination of two environmental insults rescued memory impairment (Arcego et al, 2016). Importantly, these other animal models employed different types and timing of environmental stressors on the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…An adverse maternal environment (AME) and the consumption of a western diet (WD) starting in early childhood affect health later in life (Alastalo et al, 2013; Francis & Stevenson, 2013). More specifically, human and animal studies reveal a strong association between exposure to either an AME or WD and the development of cognitive impairment and depressive disorders later in life (Alastalo et al, 2013; Arcego et al, 2016; Francis et al, 2013). AME has been shown to decreased learning and memory while maternal WD consumption has been shown to alter memory and depression in offspring (Alastalo et al, 2013; Arcego et al, 2016; de Kloet, Joels, & Holsboer, 2005; Francis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies have, however, assessed object recognition memory and spatial memory. For example, in one study pre‐pubertal stress was found to impair object recognition in adult males rats (Arcego et al, ). In the present study, prepubertal stress did not affect object recognition memory either 6‐days or 6‐weeks after the stress exposure had terminated (with the latter time point being in early adulthood).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, neonatal PCP induces long-term locomotor abnormality, cognitive dysfunction (Depoortere et al, 2005), impaired sensorimotor gating (Wang et al, 2001) and loss of parvalbumin-containing GABAergic neurones accompanied by changes in autophagy (Radonjic et al, 2013; Jevtic et al, 2016), reminiscent of features of schizophrenia. As no single rodent paradigm completely reproduces the diverse schizophrenia symptom profile, groups have started to characterize “dual-hit” models in rodents to produce more comprehensive and robust deficits, in particular of cognitive and negative features (Ashby et al, 2010; Gilabert-Juan et al, 2012; Lim et al, 2012; Giovanoli et al, 2013; Gaskin et al, 2014; Arcego et al, 2016). …”
Section: Introductionmentioning
confidence: 99%